DESIGNING ENGLISH KINESTHETIC SUPPLEMENTARY BOOK FOR MADRASAH ALIYAH STUDENTS GRADE 10 - Maya Sistiwandari (Language-Edu, 2021)
AbstractThis study is intended to design English supplementary material based on kinesthetic learning style, using Research and Development (R&D) method. This study carried out 30 subjects of the research, student Social Program grade 10 of Madrasah Aliyah Ma'arif NU Blitar, academic year of 2020/2021. The model of research was adopted from Borg & Gall (2003), which contains several steps; the first was distributing need analysis questionnaire and learning style questionnaire, in order to find the student's target needs and learning needs. The following step was designing supplementary book, then, it was validated by material expert. The next stage was trying out the product to the students. The last step was revision, and conducting last try out. The product from this study is an English complementary book, consist of six chapters. The product is equipped with several physical activities to boost student's learning motivation. The overall activity is encouraging students to be more active during class activities, since they have more suitable learning process as their personal preference. Moreover, the product is also equipped with several assignments. The tasks have to be done individually, paired, and in small group. Keywords: Designing, Kinesthetic, Supplementary Book, Madrasah Aliyah Students.